Edukasi Online Menurunkan Nyeri Dismenore di Masa Pandemi Covid-19 - Chentia Misse Issabella; Febry Heldayasari Prabandari; Yustina Ananti; Desto Arisandi (LPPM STIKES Guna Bangsa, 2022)
During menstruation, young women sometimes experience menstrual pain which is called dysmenorrhea. Dysmenorrhea can be fatal if not handled properly because it can interfere with daily activities. With the Covid-19 outbreak, the prevalence of dysmenorrhea in female adolescents in Sleman Regency has increased, causing discomfort and anxiety. Based on the results of a survey that was conducted in June-August 2020 in Sleman Regency, as many as 254 young women had experienced menstruation and it was found 186 young women (73,22%) experienced dysmenorrhea. This study aims to determine the effect of online education on reducing dysmenorrhea pain in female adolescents in Sleman Regency in 2020. This study used a Quasy experimental method. The sample used 142 young women and was divided into 2 groups with a simple random sampling technique. Statistical test using the Mann-Whitney test. The results of this study showed a decrease in dysmenorrhea pain in young women who had been given online education by four-level, while those without education decreased by one level. The results of the study show the difference between providing online education with those without education on the reduction of dysmenorrhea pain on the first-month p-value 0,000 < α= 0,05 and on the second month p-value 0,000 < α= 0,05 in Sleman Regency in 2020. It is hoped that young women can provide treatment for dysmenorrhea pain reduction with online knowledge has been obtained.